Sociodemographic and Clinical Factors Related to Admission to the Pediatric Intensive Care Unit in Patients Hospitalized with COVID-19: A Post-Pandemic Study - Rojas Hernández; Juan Pablo; Rengifo Mosquera; María Paula; Gil Artunduaga; Mónica Alexandra; Gómez Urrego; José Fernando (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background The impact of COVID-19 on children has varied over time. Although most cases are mild, some require hospitalization and admission to the Pediatric Intensive Care Unit (PICU). In the post-pandemic period, the clinical and sociodemographic profile of at-risk patients is unknown, hindering early identification and timely management. The objective was to determine sociodemographic, clinical, and comorbidity factors associated with PICU admission in hospitalized patients with COVID-19 during the post-pandemic period. Methods Analytical case-control study. Pediatric patients hospitalized with a confirmed diagnosis of COVID-19 between May 2023 and May 2025 were included. Cases were patients admitted to the PICU, and controls were those who remained hospitalized in general wards. Sociodemographic, clinical, paraclinical, and comorbidity variables were analyzed using bivariate analysis and multivariate logistic regression. Results 119 patients were included, with a median age of 0.72 years (IQR: 0.32–2.0), predominantly under 5 years of age (84.9%). The majority of patients were male (64.7%) and from urban areas (79%). The most frequent symptoms were fever (95.8%), cough (68.9%), and rhinitis (67.2%). Leukocytosis, neutrophilia, and elevated CRP were more common. Lymphopenia, thrombocytosis, anemia, elevated procalcitonin, and elevated D-dimer did not show significant differences. Pneumonia was the most common complication (43.7%), while others included refractory shock, thrombotic microangiopathy, ataxia, status epilepticus, and glomerulonephritis. Comorbidities were present in 26.9% of patients, primarily prematurity (10.9%) and neurological disease (10.1%). Viral coinfection was present in 30.3% of patients: rhinovirus/enterovirus (17.6%), respiratory syncytial virus (7.6%), parainfluenza 3 (5.9%), adenovirus (5.9%), and influenza (6.7%). In the multivariate analysis, the independent factors associated with PICU admission were age <5 years (aOR 9.83; 95% CI 2.25–42.87), dyspnea (aOR 9.94; 95% CI 3.37–29.27), and viral coinfection (aOR 12.44; 95% CI 3.94–39.26). The model showed adequate discriminative capacity (AUC = 0.878). Conclusion In the post-pandemic period, age under 5 years, dyspnea, and coinfection were identified as independent predictors of PICU admission in children hospitalized with COVID-19, with a predictive model exhibiting very good discriminative capacity.